Hubungan pola asuh dengan kejadian stunting (rekomendasi pengendaliannya di Kabupaten Lebong) - Nur Hidayah; Wismalinda Rita; Betri Anita; Fiana Podesta; Sandy Ardiansyah; Aning Tri Subeqi; Sri Lilestina Nasution; Frensi Riastuti (Riset Informasi Kesehatan, 2019)
Background: Lebong is the third highest district (34.4%) of stunting cases in Bengkulu Province, where the percentage of children under five is very short (11.8%) in Bengkulu2. The purpose of this study was to analyze the associated of parenting to stunting to children with ages 6-59 months and its control recommendation in Lebong district. Method: The type of research used was observational analytic, case control study design and purposive sampling technique. The population is mother and children with ages 6-59 months in August 2018. Quantitative data analysis (univariate and bivariate). Results: Stunting respondents in Lebong district had a history of parenting: non exclusive breastfeeding (55.20%), time for complementary feeding <6 months (55.20%), used poor health services (72.40%), low level of maternal knowledge (67.20%), poor environmental sanitation (77.60%) & poor psychosocial stimulation (94.80%). There was a relationship (P value <0.05) between history of breastfeeding, time of giving complementary feeding, utilization of health services, level of knowledge of mother, environmental sanitation, psychosocial stimulation to stunting in Lebong. Conclusion: Three factors dominant of parenting have influence to stunting in Lebong are utilization of health services, level of mother knowledge and psychosocial stimulation. The model of controled stunting risk factors in Lebong can be done through family empowerment aimed at the individual, community and health service levels. Keywords: lebong, model, parenting style, stunting